Host NLRP6 exacerbates graft-versus-host disease independent of gut microbial composition - Toubai, Tomomi (Nat Microbiol, 2019)
Host NOD-like receptor family pyrin domain-containing 6 (NLRP6) regulates innate immune responses and gastrointestinal homeostasis. Its protective role in intestinal colitis and tumorigenesis is dependent on the host microbiome. Host innate immunity and microbial diversity also play a role in the severity of allogeneic immune-mediated gastrointestinal graft-versus-host disease (GVHD), the principal toxicity after allogeneic haematopoietic cell transplantation. Here, we examined the role of host NLRP6 in multiple murine models of allogeneic bone marrow transplantation. In contrast to its role in intestinal colitis, host NLRP6 aggravated gastrointestinal GVHD. The impact of host NLRP6 deficiency in mitigating GVHD was observed regardless of co-housing, antibiotic treatment or colonizing littermate germ-free wild-type and NLRP6-deficient hosts with faecal microbial transplantation from specific pathogen-free wild-type and Nlrp6(−/−) animals. Chimaera studies were performed to assess the role of NLRP6 expression on host haematopoietic and non-haematopoietic cells. The allogeneic [B6Ly5.2 → Nlrp6(−/−)] animals demonstrated significantly improved survival compared to the allogeneic [B6Ly5.2 → B6] animals, but did not alter the therapeutic graft-versus-tumour effects after haematopoietic cell transplantation. Our results unveil an unexpected, pathogenic role for host NLRP6 in gastrointestinal GVHD that is independent of variations in the intestinal microbiome and in contrast to its well-appreciated microbiome-dependent protective role in intestinal colitis and tumorigenesis.